1982
DOI: 10.1104/pp.70.6.1641
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Changes that Occur during Senescence of Wheat Leaves

Abstract: Changes in activities of photosynthetic enzymes and photochemical processes were followed with aging of vegetative and flag leaves of wheat (Triticum aestivum L. cv Roy). Activities of stromal enzymes began to decline prior to photochemical activities. In general, total soluble protein and the activities of ribulose-1,5-bisphosphate carboxylase and NADPtriose-phosphate dehydrogenase decUned in parallel and at an earlier age than leaf chlorophyll (Chl), leaf photosynthesis, and photosynthetic electron transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
1
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 17 publications
5
55
1
1
Order By: Relevance
“…2). Similar results were reported by Camp et al (3) in senescent wheat leaves. Also, Makino et al (21) found a strong correlation between Rubisco and ribulose 5-phosphate kinase during leafsenescence.…”
Section: Retardative Decrease In Rubiscosupporting
confidence: 82%
See 1 more Smart Citation
“…2). Similar results were reported by Camp et al (3) in senescent wheat leaves. Also, Makino et al (21) found a strong correlation between Rubisco and ribulose 5-phosphate kinase during leafsenescence.…”
Section: Retardative Decrease In Rubiscosupporting
confidence: 82%
“…Several quantitative analyses indicated that decrease in photosynthesis under ambient air conditions can be predicted from changes in the amounts and kinetics of Rubisco (5,23). Electron transport activities and the reaction-center complexes also decreased during leaf senescence, and their positive correlations with photosynthesis have been frequently reported (3,(12)(13)(14). Thus, it can be expected that a decline in photosyn- 'This work was supported in part by Grants-in-Aid for International Scientific Research (63044018) from the Ministry ofEducation, Science and Culture of Japan.…”
mentioning
confidence: 99%
“…These results are similar to those obtained with barley (7). Recently, Camp et al (6), using wheat leaves, reported that the change in Chl content most closely paralleled the change in photosynthesis and RuBP carboxylase activity was not highly correlated with photosynthesis. One possible reason for this discrepancy is the difference between the photosynthetic measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…Friedrich and Huffaker (7) and Peoples et al (24) found that loss of carboxylase activity during senescence is caused by loss of enzyme protein, whereas no correlation between them was reported by Hall et al (9). However, Camp et al (6) have recently reported that RuBP carboxylase activity decreases at a much faster rate than the photosynthetic rate during senescence. Thus, the role of RuBP carboxylase responsible for the change in photosynthesis with leaf age remains uncertain.…”
mentioning
confidence: 90%
“…However, our findings raise the question whether the decreases in plastid DNA during senescence occur on a per-plastid basis, as suggested in rice (Sodmergen et al, 1991), or whether they are due to the destruction of entire plastids. Although reduced chloroplast numbers are observed in some species throughout the senescence process (Lamppa et al, 1980;Camp et al, 1982;Wittenbach et al, 1982;Kura-Hotta et al, 1990), in other species plastid function is uniformly impaired during early senescence and whole plastids are lost only late in the process (Mae et al, 1984;Wardley et al, 1984;Ford and Shibles, 1988). This topic has not yet been investigated in tobacco.…”
mentioning
confidence: 99%